increase in the Corncrake Crex crex population of the United Kingdom has slowed - Wotton, Simon R; Eaton, Mark; Ewing, Steven R; Green, Rhys E (Bird study, 2015)
Capsule The UK Corncrake population increase has slowed, but has rapidly recovered from a large decline in 2013. Aims To provide an update on the population size and distribution of breeding Corncrakes in the UK, including the results of the most recent full national survey and annual monitoring of the core population. Methods A full survey of singing Corncrakes was undertaken in the UK and the Isle of Man in 2009, following the last full censuses in 1978/79, 1988, 1993, 1998 and 2003. Monitoring of singing male Corncrakes within the core range in northern and western Scotland has been undertaken annually since 1993. Results The 2009 results show that numbers increased substantially since 2003, from 829 to 1166 singing males. Corncrake numbers in the core range have increased in 17 of the 21 years between 1993 and 2014, and peaked at 1274 singing males, in 2014. Numbers of singing males dropped by 24% between 2012 and 2013, probably due to a particularly cold spring in 2013 that inhibited growth of vegetation cover, but numbers recovered markedly in 2014. Conclusion The recovery of the UK Corncrake population has continued since a low point in 1993. However there are no signs of range expansion into mainland UK, away from the core breeding areas in Scotland. The large decline in the core population between 2012 and 2013 highlights the sensitivity of the population to external factors, although the subsequent increase in 2014 shows a capacity for rapid recovery.